A comparative study of Sr-loaded nano-textured Ti and TiO2 nanotube implants on osseointegration immediately after tooth extraction in Beagle dogs - Li, Yongfeng; Tang, Li; Shen, Mingming; Wang, Zhen; Huang, Xiaofeng (Frontiers in Materials, 2023)
Dental implantation when performed immediately after tooth extraction simplifies the treatment procedure, resulting in dentist and patient satisfaction. Dental implants with nano-topography surface modification have been used to promote osseointegration immediately after implantation. We compared two different nano-topography surface implants on the effects of osseointegration immediately after tooth extraction: TiO2 nanotubes (NT -TiO2) fabricated by anodization and Sr-loaded nano-topography Ti (NT-Sr) formed via magnetron sputtering technology. Sr-loaded nanotextured Ti nanotubes (NT-Sr) were fabricated via magnetron sputtering using 99.99% SrTiO3 as the sputtering target. TiO2 nanotubes (NT–TiO2) were fabricated by anodization in 0.5 wt% hydrofluoric acid (HF). After surface topography, hydrophilicity, chemical components, and interface bonding strength were analyzed, two different nano-topographies were applied for in vivo cellular activity evaluation. Subsequently, the implants with NT-Sr and NT -TiO2 surfaces were inserted into the fresh socket immediately after tooth extraction. Radiological scanning, histological analysis, and biomechanical tests were carried out to investigate implant osseointegration. The results showed that nanotubes with diameters of 15–80 nm were distributed on the NT-TiO2 surface, while the NT-Sr group showed 20–40 nm nanoparticles. Compared to NT-Sr, the NT-TiO2 surface possessed better hydrophilicity and favorable cellular adhesion and proliferation. The NT-Sr surface possessed greater interfacial bonding strength than that in the NT-TiO2 group, and greater bone formation, higher bone-to-implant contact (BIC%), and maximum pull-out force were observed in the NT-Sr group. The above results indicated that although NT-TiO2 surface showed favorable in vitro bioactivity, the NT-Sr surface with higher interface bonding strength showed better in vitro osteogenesis, and were more favorable for immediate implantation.